When to push the envelope? Corruption, human rights and the request for an advisory opinion by the SERAP to the African Court (African Human Rights Yearbook / Annuaire Africain des Droits de l’Homme, 2022)
ABSTRACT:The debate on whether corruption is a violation of human rights has been raging unabated in academic and policy circles for far too long. Attempts to have the matter settled judicially have so far been ineffectual. Using the request by the Socio-Economic Rights and Accountability Project (SERAP) to the African Court on Human and Peoples’ Rights as well as other cases that have been filed with regional courts and quasi-judicial bodies, this case note attempts to contemplate the path human rights-corruption jurisprudence will take by analysing the influence of past decisions by other bodies on the Court. In terms of methodology, the article turns to artificial intelligence citation analysis for an in-depth discussion. TITRE ET RÉSUMÉ EN FRANCAIS:Quand repousser les limites? Corruption, droits de l'homme et demande d’avis consultatif du SERAP à la Cour africaineRÉSUMÉ:La corruption comme violation des droits de l'homme a fait débat depuis trop longtemps dans les cercles universitaires et politiques. Les tentatives d’une solution judiciaire à la question ont jusqu'à présent été vaines. En utilisant la demande d’avis consultatif introduite par Socio-Economic Rights and Accountability Project (SERAP) devant la Cour africaine des droits de l'homme et des peuples ainsi que d'autres affaires portées devant des juridictions régionales et des organes quasi judiciaires, cet article tente de prédire la direction que prendra la jurisprudence relative aux droits de l'homme et à la corruption en analysant l’influence sur la Cour, des décisions antérieures prises par d'autres. En termes de méthodologie, l'article se tourne vers l'analyse des citations par intelligence artificielle pour une discussion approfondie.
Keywords: African Court on Human and Peoples’ Rights; complementarity; corruption; case citation networks; SERAP request